High-intensity intermittent running and field hockey skill performance in the heat - Sunderland, C.; Nevill, M. E. (Journal of Sports Sciences, 2005)
Nine well-trained, unacclimatized female hockey players performed the Loughborough Intermittent Shuttle Test (LIST) interspersed with three field hockey skill tests in hot (30°C, 38% relative humidity) and moderate (19°C, 51% relative humidity) environmental conditions. Field hockey skill performance declined in both the hot and moderate conditions following 30 and 60?min of the LIST compared with pre-LIST values (P <0.01). This decrement in performance was compounded in the hot environment with a 6% poorer performance in the heat recorded for the second skill test at 30?min (P <0.05, hot 101.7±3.6 vs moderate 95.7±2.9 s; mean ±?sx). However, no difference was found in the decision-making element of the skill test. Fifteen-metre sprint times were slower in the hot condition (P ?<?0.01). In the hot environment, rectal temperature (P?<?0.01), perceived exertion (P<0.05), perceived thirst (P?<?0.01), blood glucose concentration (P<0.05) and serum aldosterone concentration (P?<?0.01) were higher. Estimated mean (±sx) sweat rate was higher in the hot trial (1.27±0.10l·h-1) than in the moderate trial (1.05±0.12l·h-1) (P<0.05). Body mass was well maintained in both trials. No differences in serum cortisol, blood lactate, plasma volume or plasma ammonia concentrations were found. These results demonstrate that field hockey skill performance is decreased following intermittent high-intensity shuttle running and that this decrease is greater in hot environmental conditions. The exact mechanism for this decrement in performance remains to be elucidated, but is unlikely to be due to low glycogen concentration or dehydration.